Nurturing Readership Skills in the Digital Age: Contributions of the Reading Tent Project in Njoro, Kenya - Makenzi, Margaret; Ongus, Raymond Wafula; Nyamboga, Constantine Matoke (Journal of Information and Knowledge, 2014)
The Reading Tent Project (RTP) was instituted in November 1999 as an outreach programme of the Research and Extension Division at Egerton University in Njoro, Kenya. The project, which is funded by the Rockefeller Foundation, aims at promoting a lifetime reading culture and improving pupils’ reading skills. A control group of 1567 pupils currently in classes 4 and 5 from ten selected rural primary schools within Njoro Division was closely monitored for three consecutive years. R.T.P events involved teaching elementary reading skills interspersed with educational games, modelling, drawing and painting. The project supplemented reading activities with introduction to information technology (IT) involving computers with associated accessories, assorted educational CD-ROM "talking books ", email and the Internet. Through guided exploratory sessions, improvement in the reading habits of the pupils was manifested. Moreover, through the project, some pupils established electronic links to friends abroad to share scarce educational resources. This paper exemplifies a case that developing countries can use to prepare their young citizens for an information-intensive future, thus bridging the digital divide.